Processing and Marketing of Rice-Derived Products in the Township of Natitingou, Benin (International Journal of Scientific Research and Management (IJSRM), 2021)
In view of the profound changes that have taken place in agriculture, rice has become a major consumer crop. Thus, in addition to its important role in food security, rice is increasingly being transformed into small-scale by-products that are still poorly understood and marketed. The objective of this research is to study the process of transformation and commercialization of rice products in the township of Natitingou. The methodological approach adopted consists essentially of collecting data from 78 actors, mainly processors and traders of rice derivatives, processing the data and analyzing the results obtained using the SWOT model. The analysis of the results revealed that the process of processing rice derivatives in Natitingou takes into account the parboiling of rice during its transformation, the transformation of parboiled rice into a derived food product, the hygiene rules observed in the processing room and the fermentation of rice flour for consumption. Nearly 80% of those surveyed said that rice derivatives are processed with archaic tools, and marketing is not very profitable. Despite this situation, rice processing has made it possible to obtain several by-products such as cookies, cakes, akpan, and even tchoucoutou or tchapkalo, etc. Finally, the marketing of these products is done through the marketing used by the groups, the strategies of sale and distribution price of the products derived from rice, the publicity and means of communication for the sale of these products.